Ontix: Blockchain-Based NFT Decentralized e-Ticketing Development - Elizabeth Nathania Witanto; Christopher Andreas; Rudi Limantara; Louis Fernando; Lie Samuel Miracle Kristanto; Richie Reuben Hermanto (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2026)
Event ticketing systems, such as concerts, festivals, and sports matches, face persistent challenges, including ticket forgery, duplication, resale manipulation, and fraud in secondary markets. Centralized electronic ticketing systems, while digitized, remain vulnerable to identity theft, seller unaccountability, and unfair distribution due to their reliance on intermediaries and a single point of failure. To address these issues, this research introduces Ontix, a decentralized blockchain-based e-ticketing platform utilizing Non-Fungible Tokens (NFTs) compliant with the ERC-721 standard. By leveraging blockchain’s immutability, transparency, and decentralization, Ontix ensures verifiable ownership, tamper-proof ticket issuance, and automated transactions through smart contracts. The system enforces anti-scalping measures, including resale time and price limits, while enabling real-time QR-based validation directly linked to smart contracts. Ontix integrates Layer-2 Optimism Sepolia for scalability and lower gas fees, and employs the InterPlanetary File System (IPFS) via Pinata for decentralized metadata storage, alongside Cloudinary for media management. This hybrid architecture guarantees transparency, security, and operational efficiency. By eliminating intermediaries and automating ticket lifecycle management, Ontix provides an accountable, tamper-resistant, and low-cost e-ticketing ecosystem, as well as a user-centric ticketing ecosystem, representing a significant advancement toward the future of decentralized event management.